1981
DOI: 10.1042/bj1970245
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of sarcoplasmic-reticulum adenosine triphosphatase of rabbit skeletal muscle

Abstract: Antibody was raised in chickens against purified sarcoplasmic-reticulum Ca2+-activated ATPase (Ca2+-ATPase). The immunological relationship between the Ca2+-ATPase of fast-muscle and slow-muscle sarcoplasmic reticulum was investigated by a one-step and a two-step competitive enzyme-linked immunosorbent assay (ELISA). The results show marked antigenic differences between the membrane-bound Ca2+-ATPase of the sarcoplasmic-reticulum vesicles from fast muscle and slow muscle, beside differences in the membrane con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…This may result from the specific activity of the calcium ATPase, the membrane density of the ATPase, or amounts of SR membrane in the fibers. Antibody studies suggest that the ATPase is not identical in all muscles (DeFoor et al, 1980;Damiani et al, 1981;Volpe et al, 1982), while polyclonal antibody and freeze-fracture studies suggest that there is 50% less ATPase in slow-twitch fibers (Beringer, 1976;Bray & Rayns, 1976;Heilmann, Mtiller & Pette, 1981;Jorgensen et al, 1982b). In contrast, ATPase crystal lattices (Dux & Martonosi, 1984) suggest that the different ATPase activities depend on the greater amount of ATPase containing membrane in faster fibers (Eisenberg & Kuda, 1976;Eisenberg, 1983).…”
Section: Introductionmentioning
confidence: 93%
“…This may result from the specific activity of the calcium ATPase, the membrane density of the ATPase, or amounts of SR membrane in the fibers. Antibody studies suggest that the ATPase is not identical in all muscles (DeFoor et al, 1980;Damiani et al, 1981;Volpe et al, 1982), while polyclonal antibody and freeze-fracture studies suggest that there is 50% less ATPase in slow-twitch fibers (Beringer, 1976;Bray & Rayns, 1976;Heilmann, Mtiller & Pette, 1981;Jorgensen et al, 1982b). In contrast, ATPase crystal lattices (Dux & Martonosi, 1984) suggest that the different ATPase activities depend on the greater amount of ATPase containing membrane in faster fibers (Eisenberg & Kuda, 1976;Eisenberg, 1983).…”
Section: Introductionmentioning
confidence: 93%
“…The soleus and semitendinosus muscles of male New Zealand White rabbits were used as representative slow-twitch muscles, on account of previous characterization studies in this laboratory of the isoprotein composition of myosin and other myofibrillar proteins in whole muscle (Biral et al, 1982) and isolated, chemically-skinned fibres , of the membrane protein composition and biochemical properties of isolated SR fragments from the same muscles (Damiani et al, 1981;Salviati et al 1982 a, b), as well as because of their characteristics in SR Ca 2+-release . In each experiment, SR membranes were isolated from the pooled frozen muscles of 6-8 rabbits, using a modification (Inui et al, 1987) of the original method of Saito and co-workers (1984).…”
Section: Preparative Proceduresmentioning
confidence: 99%
“…To date, no slow-twitch fiber isomorphs have been detected for parvalbumin and calsequestrin. However, Damiani et al [18], using competitive ELISA analyses, demonstrated different affinities of anti-(CaATPase) from fast-twitch muscle for the antigens from fast and slow-twitch muscles. Likewise, these observations have been confirmed in the present study.…”
Section: Characterization Of Antibodiesmentioning
confidence: 99%